Compact UWB Textile Antenna with Multi-Phase Evolution from Single to Dual Designs (International Journal of Communication Systems and Network Technologies, 2024)
In this paper, the design and performance analysis of ultra-wideband (UWB) antennas employing flexible textile substrates are presented for wearable wireless communication systems. A threephase design strategy is adopted, beginning with a single antenna element, followed by a dualelement configuration, and finally a stub-coupled dual arrangement to mitigate mutual coupling and improve impedance bandwidth. Textile materials including nylon, leather, cotton, and silk are utilized as dielectric substrates, and their impact on impedance characteristics, resonance behavior, and bandwidth is systematically investigated. The reflection coefficient S11 results demonstrate that substrate permittivity and dielectric losses play a crucial role in shaping antenna performance. Silk and nylon substrates exhibit deeper resonances with good impedance matching, while leather provides broader operating bandwidth. Cotton, due to its higher dielectric loss, yields comparatively shallow resonances and reduced efficiency. For dual-element designs, mutual coupling effects are evident, but the incorporation of a central stub significantly enhances port isolation, maintaining S11< −10dB across the 3.1–10.6 GHz UWB band. The antennas also maintain stable radiation patterns, acceptable gain, and conformal robustness under bending conditions. The proposed textilebased UWB antenna designs confirm the feasibility of low-cost, flexible, and reliable solutions for wearable and body-centric communication applications, with the stub-coupled configuration demonstrating superior performance among the investigated cases.
Keywords: Ultra-wideband Antenna; Textile Antenna; Wearable Communication; Stub-coupled Configuration